ANALISIS PENGARUH PENDAPATAN ASLI DAERAH, INVESTASI DAN ANGKATAN KERJA TERHADAP PERTUMBUHAN PDRB PROVINSI JAWA TENGAH TAHUN 1992-2011 - Fajar Novianto, Trias; Dwi Atmanti, Hastarini (Diponegoro Journal of Economics, 2013)
Economic growth of a region can be measured by the Gross Domestic Product (GDP). Economic growth in Central Java region during the observation period tends to be fluctuative and lower than any other economic growth in Java’s other region.. This research purposed to analyse local revenue, investments (in this case, investment can be observed based on Foreign Investments and Domestic Investments) and the number of labor force against economic growth in Central Java during 1992 – 2011. This research using double linear regression model and Ordinary Least Square (OLS) method to analyze data.. This research using time series data, start from 1992 until 2011. Research methods using multiple regression analysis approach, which is using 20 years periodical data. The result of data analysis indicate that local revenue, foreign investments and labor force are likely to give positive and significant effect towards GDP in Central Java. Based on F Test’s result under reliability rate of 95 %, F calculation determined in the amount of 41.67768 under probability values 0,0000. It means that the previous variable (local revenue, foreign investments, and labor force) simultanously affects the GDP in Central Java region.